2020
DOI: 10.1002/jsfa.10102
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the chemosensory basis of flavor in table grapes

Abstract: BACKGROUND: The full flavor of grape berries is determined by the interaction of sugars, acids, volatile compounds, and other berry properties, such as astringency. Sugars and acids are important for berry taste, whereas volatile compounds are important for the unique berry flavors, e.g., monoterpenes for the Muscat varieties. RESULTS: We explored the basis for 'fruity' flavor perception in table grapes. Samples were collected from 134 new table grape lines and commercial varieties and tested chemically for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 92 publications
(125 reference statements)
2
19
0
Order By: Relevance
“…They are derived from linoleic and linolenic acid and have been described as the basic background volatiles in table grape berries [ 5 , 20 ]. Among them, it was found that hexanal and ( E )-2-hexenal were the major compounds in all the grape varieties, which was in agreement with previous studies [ 11 , 21 , 22 ]. The amount of hexanal found in Krissy was significantly lower than the quantities present in the other four varieties analyzed.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…They are derived from linoleic and linolenic acid and have been described as the basic background volatiles in table grape berries [ 5 , 20 ]. Among them, it was found that hexanal and ( E )-2-hexenal were the major compounds in all the grape varieties, which was in agreement with previous studies [ 11 , 21 , 22 ]. The amount of hexanal found in Krissy was significantly lower than the quantities present in the other four varieties analyzed.…”
Section: Resultssupporting
confidence: 91%
“…The amount of hexanal found in Krissy was significantly lower than the quantities present in the other four varieties analyzed. The ratio of hexanal to ( E )-2-hexenal was recently correlated with sweetness [ 22 ], and these compounds have also been quoted as the most active C6 compounds in table grapes and, therefore, are important contributors to the perceived aroma of this fruit [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the concentration of benzaldehyde decreased at a slower rate and later in affected than in non-affected cherries (after stage 4), but the total content was higher at phenological stage 5 in the affected cherries. The C6 aldehydes hexanal and (E)-2-hexenal have been well described as green-herbaceous contributors to the aroma and flavor of fruits [40,41], and they are produced from fatty acids through the lipoxygenase (LOX) pathway [42,43]. There were no significant differences in the levels of these compounds between the affected and non-affected cherries within the same orchard (considering the six localities).…”
Section: Aldehydesmentioning
confidence: 99%
“…Aprea et al [14] observed a negative contribution of 3-hexenol to the sweet perception of apple, whereas Klee and Tieman [47] reported a positive contribution to the 'overall flavor intensity' and 'liking' of tomato. Other authors observed the negative contribution of hexenal to the 'overall flavor intensity' and 'liking' of strawberries and blueberries [47], as well as to the sweetness of table grapes [48]. Besides, the interactions between certain VOCs with sugars and acids affect the rate of release and persistence of these volatile compounds in the mouth and, thus, the perceived intensities of aroma and flavor attributes [15].…”
Section: Effect Of Ssc Ph and Volatiles Over Sweetness Acidity And Astringency Attributesmentioning
confidence: 99%